Ethics of decisionism: Carl Schmitt's theological blind spot. Issue 3 (2nd July 2016) - Hoelzl, Michael
Abstract : In his elaborate historical study Die Diktatur of 1919, C. Schmitt prepares the grounds for his famous definition of sovereignty. S overeign, as Schmitt will write in his Political Theology five years later, is the one who decides on the state of exception . The following essay analyses the theological origins of Schmitt's understanding of sovereignty. The problem of sovereignty and his controversy with Hans Kelsen's programme of legal positivism is the starting point for Schmitt to formulate a general outline of a theory of decisionism. Decisionism as political theory is based on the concept of a rightful deviation from law by personal decision-making in concrete circumstances. The problem of a rightful deviation from law, which will be the focus of my attention, is a well-known problem in legal philosophy and theology. In the following essay, it will be demonstrated how Schmitt evades the theological nature of the problem by drawing attention to Die Diktatur in which the problem of a rightful deviation from law was first systematically analysed. The essay does not primarily intend to explain the absence of the theological and ethical discourses about rightful deviation from law in Schmitt's work. The aim of the essay is rather to detect a "blind spot" in Schmitt's general outline of a theory of decisionism and to contribute to a more nuanced understanding of decisionism as theo-political theory.